Type of themes and thematic progression patterns in low achiever's descriptive writings - Siahaan, Elsa Maulita; Amalia, Rosaria Mita; Krisnawati, Ekaning (Diksi, 2023)
The Low Achiever's writing is frequently categorized as the low coherent text due to the quality of their writings based on the rubric used at school. Hence, the focus in this study is to analyze the Types of Theme and Thematic Progression patterns found in Low Achiever's Descriptive Writings with descriptive-qualitative research design. The objective is to observe the coherency quality of low achiever's based on the analysis of Theme and Thematic Progression. The steps are selecting two low achiever's descriptive texts based on the school's rubric, dividing them to clauses, analyzing both the Theme and the Thematic progression, then providing the results of the analysis. The result shows that all types of Themes and Thematic Progressions are found in both writings. The Unmarked Topical Theme and Constant Theme Patterns are most frequently used. The conclusion is that Low Achiever's Descriptive Writings cannot be considered as a low-coherent text based on School's rubric only, Theme and Thematic Progression analysis is suggested to be conducted for extra observation and evaluation despite of the easy and common themes many constant types used to start the clauses in both of their writings. Keywords: descriptive text, low achiever's writings systemic functional linguistics, theme, and thematic progression